(untitled) (Nativa, 2024)
The planning for developing coffee-growing regions has been carried out in various areas, involving multiple stakeholders as part of agricultural development efforts. Similarly, in the planning process for these coffee-growing regions, it is crucial to involve local communities as the owners of coffee farmland. However, preliminary surveys indicate that community involvement in planning remains significantly limited. This study analyzes how community empowerment contributes to the planning and development of coffee-growing regions. The research was conducted in Kepahiang Regency and Rejang Lebong Regency, Bengkulu Province, as these two regencies are the largest coffee producers in the province and have established development plans for their coffee-growing regions. The study employs a mixed-methods approach, combining interactive analysis with quantitative tools such as Likert scale weighting and Structural Equation Modeling (SEM) using Partial Least Squares (PLS). The findings reveal that community empowerment has a significant positive effect, with a t-value of 19.069 (greater than the critical value of 1.96). The impact magnitude is 0.611 (61.1%), indicating that empowerment positively influences the success of coffee region development planning by 61.1%. This underscores the critical role of community empowerment in ensuring the effective implementation of development plans that align with their objectives. Keywords: agricultural development; local communities; structural equation modeling; partial least squares. Impacto do Empoderamento da Comunidade no Desenvolvimento de Áreas de Café Localizadas na Província de Bengkulu, Indonésia RESUMO: O planejamento para o desenvolvimento de regiões de cultivo de café foi realizado em várias áreas, envolvendo várias partes interessadas como parte dos esforços de desenvolvimento agrícola. Da mesma forma, no processo de planejamento para essas regiões de cultivo de café, é crucial envolver as comunidades locais como proprietárias das terras de cultivo de café. No entanto, pesquisas preliminares indicam que o envolvimento da comunidade no processo de planejamento permanece significativamente limitado. Este estudo visa analisar até que ponto o empoderamento da comunidade contribui para o planejamento e desenvolvimento de regiões de cultivo de café. A pesquisa foi conduzida em Kepahiang Regency e Rejang Lebong Regency, província de Bengkulu, pois essas duas regências são as maiores produtoras de café da província e estabeleceram planos de desenvolvimento para suas regiões de cultivo de café. O estudo emprega uma abordagem de métodos mistos, combinando análise interativa com ferramentas quantitativas, como ponderação de escala Likert e Modelagem de Equações Estruturais (SEM) usando Mínimos Quadrados Parciais (PLS). As descobertas revelam que o empoderamento da comunidade tem um efeito positivo significativo, com um valor t de 19,069 (maior que o valor crítico de 1,96). A magnitude do impacto é de 0,611 (61,1%), indicando que o empoderamento influencia positivamente o sucesso do planejamento do desenvolvimento da região cafeeira em 61,1%. Isso ressalta o papel crítico do empoderamento da comunidade em garantir a implementação eficaz dos planos de desenvolvimento em linha com seus objetivos Palavras-chave: desenvolvimento agrícola; comunidades locais; modelagem de equações estruturais; mínimos quadrados parciais.